Biogas Production from Anaerobic Digestion of Different Biodegradable Materials - Sapkota, Tika; Aryal, Jagannath; Thapa, Samir; Karki, Amrit B (Nepal Journal of Science and Technology, 2013)
This study presents the feasibility of different biodegradable materials such as kitchen wastes, water hyacinth (Eichhornia sp.), green garden grass, banana (Musa acuminate) bases, Banmara (Eupatorium adenophorum) and cabbage leaves (Brassica oleracea var. capitata) for biogas production. The experiment was conducted using 0.05 m3 anaerobic bioreactor of ARTI model compact biogas technology under ambient temperature condition in Kathmandu. The minimum and maximum temperature recorded during the study period (March 1 to July 1, 2009) was ranged from 10°C to 33°C. Total solid was found maximum (39.72 percent) in kitchen waste and minimum in cabbage leaves (8.36 percent). Volatile solid was more than 75 percent in all substrates. Organic matter ranged from 34.85 to 68.11 %. Similarly, C/N ratio was found maximum (22.57:1) in kitchen waste. Variations were observed in pH values. It was recorded between 5.7 and 6.8 in the first month but above 7 after second month of the plant installation. Burning of gas was detected after 42 days in cow dung, 52 days in water hyacinth, 80 days in kitchen waste and 70 days in banana base, Banmara, garden grass and cabbage leaves. Similarly, methane concentration after 105 days of plant installation was found to be 53 percent in cow dung, 48.8 percent in kitchen waste, 49.4 percent in water hyacinth, 24.5 percent in banana base, 38.5 percent in Banmara and 41.5 percent in garden grass. Total gas production in four months was found maximum in water hyacinth (45 l/kg TS) and minimum in cabbage (25.78 l/kg TS). The gas production in cow dung, Banana base, Banmara, garden grass and kitchen waste was therefore 41.12 l, 31.14 l, 34.02 l, 27.78 l and 32.12 l per kg of TS respectively. The purpose of designing this micro ARTI model plant was to test the feasibility of selected biodegradable materials for biogas production to be relevant in household level. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 123-128 DOI: http://dx.doi.org/10.3126/njst.v13i2.7724